Students’ Perception and Acceptance of Using Padlet as a Digital Tool for English Writing Skills - Suparmi Suparmi (Jurnal Pendidikan Humaniora, 2022)
Abstract: This study aims at investigating the students’ perception and acceptance of using Padlet in learning English writing. A total of 70 students taking the English for Specific Purposes (ESP) course at a state university in Indonesia were involved in the study. They were asked to fill out a questionnaire and 10 of them were interviewed to determine whether the students’ perception and acceptance of the use of Padlet for learning English writing as they stated in the questionnaire. The results indicated that the majority of the students had a positive perception and accepted the usage of Padlet facilitated their writing process. The students find Padlet helpful in learning English writing, as it accommodates their English writing activities, improves their English writing skills, and motivates them to learn English writing.Abstrak: Penelitian ini bertujuan untuk mengetahui persepsi dan penerimaan siswa terhadap penggunaan Padlet dalam pembelajaran menulis bahasa Inggris. Sebanyak 70 mahasiswa yang mengambil mata kuliah English for Specific Purposes (ESP) di salah satu perguruan tinggi negeri di Indonesia terlibat dalam studi tersebut. Mereka diminta untuk mengisi angket dan 10 orang di antaranya diwawancarai untuk mengetahui apakah persepsi dan penerimaan mahasiswa terhadap penggunaan Padlet untuk pembelajaran menulis bahasa Inggris seperti yang mereka nyatakan dalam angket. Hasil penelitian menunjukkan bahwa sebagian besar mahasiswa memiliki persepsi positif dan menerima penggunaan Padlet untuk memfasilitasi proses menulis mereka. Para mahasiswa merasa Padlet membantu dalam belajar menulis bahasa Inggris, karena mengakomodasi kegiatan menulis bahasa Inggris mereka, meningkatkan keterampilan menulis bahasa Inggris mereka, dan memotivasi mereka untuk belajar menulis bahasa Inggris.